On the edge of the desert - a Namaqualand story: 1800-1909 - Kelso, Clare Joanne (My University, 2010)
This research aims to identify the causes of impoverishment of the rural community of Leliefontein in Namaqualand during the 19th century. This is achieved through integrated, multi-disciplinary environmental assessment, in which the drivers of decline, both climatic and socio-economic are identified. The primary research is predominantly archival making use of historical documentary sources. The study includes two parts: a full reconstruction of the climate of the Namaqualand area using historical documentary sources and a detailed socio-economic history. To achieve the climatic reconstruction a proxy precipitation data set is compiled for the Namaqualand area using historical documentary sources. This data set is graphically represented and the notable periods of severe drought identified include: 1805; 1807; 1812; 1817; 1820-1821; 1825-1827; 1834-1836; 1844-1845; 1855-1857, 1860-1862; 1865-1868; 1874- 1875; 1880-1883; 1893-1896. The documentary derived data set is tested for accuracy against available rainfall data for the period spanning 1878-1900 and overall a close correlation is revealed. In addition, widespread droughts were identified using other similar studies and possible co-incidence with El Niño Southern Oscillation low phase events is postulated. Drought frequency and intensity is revealed to have been similar throughout the 19th century however, the ability of the Leliefontein Namaqua population to cope with these droughts declines sharply. The reasons for this emerge though the second part of the research, the historical livelihoods and vulnerability study. The community experience decline from sustainable livelihoods at the beginning of the 19th century to poverty and famine by the end of the period. This deterioration is not constant and the period spanning 1816-1853 shows relative improvement due to nomadic pastoral livelihoods and the addition of seasonal agriculture. However, increased diversity of livelihoods and increased exposure to external economic factors result in rapid decline in the second half of the century. Exploitative cattle trade, encroachment and settlement by the colonial population, the introduction of agriculture, copper mining and the introduction of wage labour, the growth of a cash based economy and the restriction of land availability for transhumance lead to a dramatic decrease in community resilience in the second half of the century, resulting in each successive drought having worse effects. Finally, the role of the written word in representing the Namaqua population is interrogated. The function of Colonial scripting in justifying exploitative policy making and legitimating the expropriation of land and the extraction of labour is interrogated. This integrated study reveals the importance of including both human and anthropogenic factors in environmental historigraphy. Socio-economic changes and disempowerment drive the decline in Namaqualand, but climatic factors severely compound this and hasten the decline.